Anne Geisz: capstone - Geisz, Anne, artist (Colorado State University. Libraries, 2021)
The artist's statement: My work seeks to understand and represent fractions of the human form. So often, we focus on our inner experiences and thoughts instead of the impact of our physical bodies and their actions. Each moment our body encounters leaves a lasting imprint on the space it occupies. My intent is to bring forward the importance of these moments and explore their subtle nuances. I am drawn to the material of clay for its capacity to hold. It is something that is capable of holding an imprint, an idea, or an object. We are able to mold and shape it, yet it still possesses boundaries and limits. Similarly, the human form is capable of holding both internally and externally. Our bodies hold our consciousness and organs while also holding onto the world around them. In this way they act much like a ceramic vessel that is meant to fulfill a dual purpose; to have both an aesthetic value and act as a tool for practical life. This body of work considers what it means to hold and serves as a bridge between aesthetic merit and functionality. Each piece contains life both through its inherent existence and through its function as a vase.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery